Sudden Infant Death Syndrome, Infection, Prone Sleep Position, and Vagal Neuroimmunology - Goldwater, Paul Nathan (Frontiers in Pediatrics, 2017)
Recent findings suggest that infection (and sepsis) stand alone as the only plausible mechanism of causation of sudden infant death syndrome (SIDS) and accordingly achieves congruence with all clinicopathological and epidemiological findings. This review examines the role of infection in the pathogenesis of SIDS in the context of the major risk factor of prone sleep position. The paper explores how sleep position could interact with the immune system and inflammatory response via Vagal neural connections which could play key roles in gut and immune homeostasis. A plausible and congruent clinicopathological and epidemiological paradigm is suggested.